The relationship between morpho‐physiological changes and expression of transcription factors in NTT local rice cultivars as a response to drought stress - Yustina Carolina Febrianti Salsinha; Alfino Sebastian; Ekris Sutiyanti; Yekti Asih Purwestri; Didik Indradewa; Diah Rachmawati (Universitas Gadjah Mada, 2022)
Response by plants to drought occurs through a series of mechanisms that involve transcription regulation. This research was conducted to study transcription factors (TF) and physiological changes in the drought response of local rice cultivars from East Nusa Tenggara (Nusa Tenggara Timur, NTT) during drought stress. Using three NTT local rice cultivars (Boawae Seratus Malam (BSM), Gogo Jak (GJ), and Kisol Manggarai (KM)) and the fraction of transpirable soil water (FTSW) method with two treatment levels, FTSW 1 (control) and FTSW 0.2 (severe stress), we analyzed the TF expression of OsDREB1A, OsDREB2A, OsWRKY45, and OsNAC6. Based on the result, the highest level of TF expression occurred in the BSM, followed by the GJ and KM cultivars. Analysis of physiological characteristics showed an association between TF expression levels and physiological response, with the BSM cultivar showing high pigment levels, high proline content, and lower H2O2 levels. A linkage was also found in relation to water conservation, as indicated by the higher relative water content and cell membrane stability index in the BSM cultivar in contrast to lower electronic leakage and malondialdehyde percentage when exposed to drought. Based on the results, it can be concluded that the BSM cultivar can be considered as a drought‐tolerant local cultivar according to morpho‐physiological analysis. In this study, all NTT local rice cultivars showed a subtle upregulation of stress‐responsive transcription factors OsDREB1A, OsDREB2A, OsWRKY45, and OsNAC6 as responses to drought stress.